4x+23=12x-73

Simple and best practice solution for 4x+23=12x-73 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+23=12x-73 equation:


Simplifying
4x + 23 = 12x + -73

Reorder the terms:
23 + 4x = 12x + -73

Reorder the terms:
23 + 4x = -73 + 12x

Solving
23 + 4x = -73 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
23 + 4x + -12x = -73 + 12x + -12x

Combine like terms: 4x + -12x = -8x
23 + -8x = -73 + 12x + -12x

Combine like terms: 12x + -12x = 0
23 + -8x = -73 + 0
23 + -8x = -73

Add '-23' to each side of the equation.
23 + -23 + -8x = -73 + -23

Combine like terms: 23 + -23 = 0
0 + -8x = -73 + -23
-8x = -73 + -23

Combine like terms: -73 + -23 = -96
-8x = -96

Divide each side by '-8'.
x = 12

Simplifying
x = 12

See similar equations:

| 3x+4=59 | | 12-3=10x+3 | | y+34=18 | | 7+2x^2+4x^2=37 | | 5(5x+13)=25 | | 9m+3(m+12)-2= | | 0.45x+.05(2-x)=.10(-55) | | 4x(1-3x)=0 | | 5x+2=-5x+12 | | y=x^2-4x-1 | | 7z-8z=8z-6+4z | | 6w+13=3w-26 | | 3(2x+3)-5= | | -7(1)(-7)= | | 8x=18+5x | | 8x-2=40x+6 | | 3(5x+7)=-48+9 | | 48-x=7-4x | | 2a+6+9a+8= | | 10x-(3x-11)=25 | | x+4=59 | | 9x(x-5)=20x^2-46X | | 4+x=120 | | (2x-5)=5 | | 20-5n= | | 6(x-3)+3=2x+5 | | (x^2-x-2)(2x+3)=0 | | Q=15-0.5*29.267 | | 150*68= | | 23y+25=25y-4 | | -27=y | | -0.3x+0.2x-4=-2 |

Equations solver categories